Estableciendo la autoridad del rey católico en Asia oriental: la erección del obispado de Manila (años 1570-1590) - Guillaume Gaudin (Caravelle)
In this paper, I present one of my focus of research dealing with remote government as part of the Hispanic Monarchy: analyzing Philippines’ case, I try to identify the mechanisms of connections between different parts of the “empire” and the options followed – or rather the trial-and-error methods – to establish a Castilian dominion in Asia. One aspect of this issue lies in the role of religious institutions within the government, specially the bishop’s and diocese’s role, while in Asia relations with the Portuguese were still at odds. I study the geopolitical implications of the creation of Manila’s diocese, and how the bishopric was an adjustement variable in the search for a good government in the Philippines. I also try to explain Domingo de Salazar’s appointment as first bishop of the Philippines, a Dominican friar, defender of the Indians, who turned out to be a real statesman.